2013
DOI: 10.1634/theoncologist.2012-0339
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Early Hypertension and Clinical Outcome With Bevacizumab: Results From Seven Phase III Studies

Abstract: Background. Hypertension is associated with antivascular endothelial growth factor treatment, but the clinical implications of hypertension are uncertain. To assess the prognostic and predictive value of bevacizumab-related hypertension, a comprehensive analysis of whether hypertension and efficacy outcomes are associated was conducted on seven companysponsored placebo-controlled phase III studies of bevacizumab. Methods. Patient-specific data were available from 6,486 patients with metastatic colorectal, brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 33 publications
5
60
2
1
Order By: Relevance
“…No association was found between clinical benefit (RR or 16-week PFS) from aflibercept and the presence of hypertension. This is consistent with results from an analysis of seven phase III trials of bevacizumab; early treatment-related blood pressure increases did not predict for benefit from bevacizumab based on PFS or overall survival [Hurwitz et al 2013]. …”
Section: Phase IIsupporting
confidence: 87%
“…No association was found between clinical benefit (RR or 16-week PFS) from aflibercept and the presence of hypertension. This is consistent with results from an analysis of seven phase III trials of bevacizumab; early treatment-related blood pressure increases did not predict for benefit from bevacizumab based on PFS or overall survival [Hurwitz et al 2013]. …”
Section: Phase IIsupporting
confidence: 87%
“…Previous studies showed a positive link between arterial hypertension due to bevacizumab and outcome in patients with advanced colorectal cancer [49,50] and renal cell cancer [51] or related to axitinib in pancreatic cancer [52] . However, a recent systematic review of all placebo-controlled phase Ⅲ trials with bevacizumab failed to demonstrate any positive impact of drug-related arterial hypertension and clinical benefit [progressionfree survival (PFS) and OS] in patients with advanced cancers [53] . Sorafenib-induced arterial hypertension was reported to be predictive of clinical benefit in patients with metastatic renal cell cancer [54] .…”
Section: Clinical Biomarkersmentioning
confidence: 99%
“…Hypertension has also been suggested to be a predictive marker of bevacizumab efficacy, and a retrospective analysis suggested a predictive value of hypertension as a marker of response to bevacizumab 36 . In contrast, an analysis of seven phase iii trials 37 and the results of a phase ii trial 38 reject that hypothesis. A group of Spanish oncologists are currently conducting a prospective study to explore the potential role of hypertension in predicting the efficacy (in terms of pfs) of bevacizumab associated with chemotherapy in patients with breast or colorectal cancer (see http:// www.clinicaltrials.gov/show/NCT01733628).…”
Section: Patient Profilementioning
confidence: 87%